Analyzing the effect of 25-hydroxy vitamin D level on strength and endurance in male wrestlers - Baikoglu, S. (Journal of Education and Learning, 2019)
90-95% of vitamin D which has the supreme function of regulating many metabolisms in tissues and organs, is taken from the sunlight through skin. Since wrestling is performed in sun-protected sports halls, we think that a vitamin D replacement will improve the performance of wrestlers, especially as the limited exposure to sunlight is compared to outdoor sports branches. The aim of our study is to increase the strength and endurance of male wrestlers by applying 25-Hydroxy vitamin D replacement together with general and wrestling-specific trainings for 8 weeks.